Effects of Halothane on Platelet Function - Dalsgaard-Nielsen, J; Gormsen, J (Thrombosis and Haemostasis, 1980)
Human platelets in platelet rich plasma (PRP) incubated at 37° C with 0.3–2% halothane for 5–10 min lost the ability to aggregate with ADP, epinephrine and collagen.At the same time uptake and release of 14C-serotonin was inhibited. When halothane supply was removed, platelet functions rapidly returned to normal. However, after high concentrations of halothane, the inhibition of platelet aggregation was irreversible or only partially reversible.The results suggest that halothane anaesthesia produces a transient impairment of platelet function.
Keywords: Halothane; (Inhibition of) Platelet aggregation; Serotonin uptake; Serotonin release